Analisis Faktor-Faktor yang Menghambat Proses Pembelajaran Mahasiswa Semester VI Kelas B pada Mata Kuliah Menulis Karya Ilmiah - Warisman Zebua; Festina Buulolo; Ikhlas Carlan Hulu; Noveri Amal Jaya Harefa; Mei Damai Telaumbanua (Journal on Education, 2024)
The objective of this study is to identify the factors that hinder the learning process of students in the scientific writing course at the University of Nias, Faculty of Teacher Training and Education, Indonesian Language and Literature Education Study Program, during the sixth semester. This research uses a qualitative descriptive approach and involves 23 students as respondents. Data were collected using questionnaires. The results of the study indicate that internal factors such as learning motivation, interest in learning, learning skills, cognitive abilities, and physical and mental health have a significant impact on students' learning outcomes. External factors such as family support, economic conditions, campus environment, teaching methods of lecturers, and campus facilities also affect the learning process. Generally, it was found that although most students have good learning and cognitive abilities, there are several challenges affecting their motivation, interest, and physical and mental health. External factors, such as inadequate campus facilities, uncomfortable learning environments, and ineffective teaching methods by lecturers, also contribute to hindering students' learning. This research emphasizes the importance of the campus providing sufficient support through guidance and counseling programs to help students overcome their learning difficulties, so they can achieve better learning outcomes and meet their academic goals.